Examining the impact of cement on porosity evolution in the upper triassic Kurra Chine Formation of Sirwan valley, Kurdistan region, Iraq: A study integrating cathodoluminescence and scanning electron microscopy - Mahdi K. Aswad; Muhamed F. Omer; Srood F. Naqshabandi (Kuwait Journal of Science)
The study of carbonate petrography is essential for understanding reservoir properties and the quality of rock formations. High-resolution cathodoluminescence spectroscopy and optical microscopy were used to determine the impact of cement on the porosity evolution of carbonate rocks of the Kurra Chine Formation at Sirwan Valley, Northern Iraq. This study represents the first-ever attempt to investigate sedimentology at this location. A total, of 183 thin-section slides, 18 X-Ray Diffraction (XRD) samples, 14 Scanning Electron Microscope (SEM) samples, and 6 Cathodoluminescence (CL) samples were analyzed from the outcrop section of the Kurra Chine Formation. Four types of dolomite textures are recognized and classified based on the crystal size distribution and crystal-boundary shape. The porosity within Kurra Chine Formation includes primary and secondary porosity, with the majority of primary porosity being occluded by cementation. Cathodoluminescence analysis revealed two phases of calcite cement in the Kurra Chine Formation. The first phase (C1), is characterized by weak-zoned blocky calcite, displaying a dull luminescence with typical homogenous red color, which fills most of the interparticle and moldic pores. The second type of calcite cement (C2) is ghost-zoned calcite exhibiting red to slight orange luminesces interfingering with dolomite cement. XRD analysis indicated a predominant of calcite and common dolomite. SEM analysis revealed the predominance of secondary porosity occurring within fractures of the dolomite.